Me and AAC - Alternative and Augmented Communication in West Germany from a Biographical and Media Archaeological Perspective - Jan Müggenburg; Andreas Wagenknecht (Tijdschrift voor Mediageschiedenis)
The article presents a case study on the history of Augmentative and Alternative Communication (AAC) in West Germany from the 1980s to the early 2000s, with a regional focus on the state of North Rhine-Westphalia (NRW). The conceptual framework guiding this study is the question of how the meaning and individual experience of assistance evolve in conjunction with the technical development and practical use of speech computers. The article sheds light on the interplay between historical contingency and individual socio-technical situatedness of disabled AAC-users. It brings together two disciplinary perspectives in a dialogue based on interviews, published primary sources, and the description of historical hardware and software. Biographical narratives of AAC users in NRW are combined with a media archaeological case study of the institutional and technological formations and developments of AAC in the region. We discuss assistive technologies as a historically variable phenomenon. Assistance is a precarious undertaking that is constantly renegotiated by new technological developments. Each stage of assistive technology has consequences for everyday communication practices and the provision of communicative assistance, creating possibilities and impossibilities for the use of technology. For AAC users, this means that they find themselves in specific constellations that affect both their relationship with the device and their subjective preferences and established routines.